Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.bmc.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N4-(substituted phenyl)-N4-alkyl/desalkyl-9H-pyrimido[4,5-b]indole-2,4-diamines and identification of new microtubule disrupting compounds that are effective against multidrug resistant cells

Abstract: A series of fourteen N4-(substituted phenyl)-N4-methyl/desmethyl-9H-pyrimido[4,5-b]indole-2,4-diamines was synthesized as potential microtubule targeting agents. The synthesis involved a Fisher indole cyclization of 2-amino-6-hydrazinylpyrimidin-4(3H)-one with cyclohexanone, followed by oxidation, chlorination and displacement with appropriate anilines. Compounds 6, 14 and 15 had low nanomolar potency against MDA-MB-435 tumor cells and depolymerized microtubules. Compound 6 additionally had nanomolar GI50 valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…However, compound 8 with added conformational restriction via a N5-methyl over 5 was highly potent and only 2-fold less potent than the most potent analog 7 . As with previously described pyrimidine fused bicyclic and tricyclic compounds, 15, 34, 4850 the methyl group attached to the 4-nitrogen bridge is crucial for inhibition of tubulin assembly. Removal of this N -methyl group ( 6 compared with 7 ) resulted in significant loss of tubulin inhibitory activity.…”
Section: Biological Evaluations and Discussionmentioning
confidence: 72%
“…However, compound 8 with added conformational restriction via a N5-methyl over 5 was highly potent and only 2-fold less potent than the most potent analog 7 . As with previously described pyrimidine fused bicyclic and tricyclic compounds, 15, 34, 4850 the methyl group attached to the 4-nitrogen bridge is crucial for inhibition of tubulin assembly. Removal of this N -methyl group ( 6 compared with 7 ) resulted in significant loss of tubulin inhibitory activity.…”
Section: Biological Evaluations and Discussionmentioning
confidence: 72%
“…26, 27 Development of MTAs that circumvent Pgp and/or βIII-tubulin-mediated resistance 28 could have advantages in patients who fail to respond to current MTAs. Most of the colchicine site agents circumvent Pgp and βIII-tubulin mediated resistance 28, 29 and could be beneficial. However, thus far, no colchicine site agent has been approved as an anticancer agent.…”
mentioning
confidence: 99%
“…Gangjee et al 29 reported pyrimido[4,5- b ]indole 1 (Figure 2) as a potent microtubule depolymerizer (EC 50 of 133 nM) with potent in vitro cytotoxic activity in MDA-MB-435 cells (IC 50 of 14.7 nM). Compound 1 is a colchicine site agent and it also circumvents clinically relevant Pgp and βIII-tubulin mediated resistance.…”
mentioning
confidence: 99%
See 2 more Smart Citations